2015
DOI: 10.1016/j.asr.2015.05.042
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of ballistic capture in Sun–planet models

Abstract: Analysis of ballistic capture orbits in Sun–planet systems is conducted in this paper. This mechanism utilizes purely gravitational forces, and may occur in non-Keplerian regimes. Ballistic capture orbits are generated by proper manipulation of sets of initial conditions that satisfy a simple definition of stability. Six Sun–planet systems are considered, including the inner planets, Jupiter, and Saturn. The role of planets orbital eccentricity, their true anomaly, and mass ratios is investigated. Moreover, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 31 publications
1
35
0
Order By: Relevance
“…In the literature, the ballistic capture phenomenon has mainly been studied with respect to reference frames related to the orbit of the target body; in the Radial-Tangent-Normal frame at epoch t 0 (RTN@t 0 , for brevity), centred at the target body, the z-axis (z r ) is perpendicular to the plane of the Sun orbit, the x-axis (x r ) is aligned with the Sun-planet line, pointing from the Sun to the planet and the y-axis (y r ) completes the dextral orthonormal triad. The transformation from the RTN@t 0 to the EME2000 can be found in Luo and Topputo (2015).…”
Section: Reference Framesmentioning
confidence: 99%
See 2 more Smart Citations
“…In the literature, the ballistic capture phenomenon has mainly been studied with respect to reference frames related to the orbit of the target body; in the Radial-Tangent-Normal frame at epoch t 0 (RTN@t 0 , for brevity), centred at the target body, the z-axis (z r ) is perpendicular to the plane of the Sun orbit, the x-axis (x r ) is aligned with the Sun-planet line, pointing from the Sun to the planet and the y-axis (y r ) completes the dextral orthonormal triad. The transformation from the RTN@t 0 to the EME2000 can be found in Luo and Topputo (2015).…”
Section: Reference Framesmentioning
confidence: 99%
“…Considering a system of n bodies, n − 1 of which called primaries, it is interesting to study the motion of a particle of negligible mass with respect to them. Following Luo and Topputo (2015), in order to underline the hierarchy of influence of the bodies on the motion of the particle, the motion is governed by:…”
Section: Equations Of Motionmentioning
confidence: 99%
See 1 more Smart Citation
“…It avoids large velocity changes near the asteroids to reduce the risk of execution errors or thruster failures. Ballistic capture can also save capture velocity increments by utilizing the multi-body gravities [35][36][37][38], though the effect may negligible and insignificant in binary asteroid systems. In general, the spacecraft will gradually reduce its velocity relative to the asteroid during the approaching phase.…”
Section: Capture Trajectoriesmentioning
confidence: 99%
“…The application of ballistic capture to Mars transfer has also been studied in detail [22][23][24][25]. Due to the relatively large excess velocity in Earth-Mars transfer, it was found that Hiten-like captures do not exist in the Sun-Mars system [26].…”
Section: Introductionmentioning
confidence: 99%